Post-acute COVID-19 syndrome. (9th March 2022) - Montani, David; Savale, Laurent; Noel, Nicolas; Meyrignac, Olivier; Colle, Romain; Gasnier, Matthieu; Corruble, Emmanuelle; Beurnier, Antoine; Jutant, Etienne-Marie; Pham, Tài; Lecoq, Anne-Lise; Papon, Jean-François; et al.
Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the coronavirus disease 2019 (COVID-19) pandemic that has resulted in millions of deaths and a major strain on health systems worldwide. Medical treatments for COVID-19 (anticoagulants, corticosteroids, anti-inflammatory drugs, oxygenation therapy and ventilation) and vaccination have improved patient outcomes. The majority of patients will recover spontaneously or after acute-phase management, but clinicians are now faced with long-term complications of COVID-19 including a large variety of symptoms, defined as "post-acute COVID-19 syndrome". Most studies have focused on patients hospitalised for severe COVID-19, but acute COVID-19 syndrome is not restricted to these patients and exists in outpatients. Given the diversity of symptoms and the high prevalence of persistent symptoms, the management of these patients requires a multidisciplinary team approach, which will result in the consumption of large amounts of health resources in the coming months. In this review, we discuss the presentation, prevalence, pathophysiology and evolution of respiratory complications and other organ-related injuries associated with post-acute COVID-19 syndrome. Given the millions of patients infected with SARS-CoV-2 worldwide and the need for multidisciplinary management of the chronic complications, post-acute COVID-19 syndrome will be a major issue for various healthcare providers in the coming months. https://bit.ly/3lBJuXu